2017
DOI: 10.1109/tmi.2017.2723479
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Ultrasound Imaging With Virtual Source Synthetic Aperture Focusing and Coherence Factor Weighting

Abstract: Intravascular ultrasound (IVUS) has been frequently used for coronary artery imaging clinically. More importantly, IVUS is the fundamental image modality for most advanced multimodality intravascular imaging techniques since it provides a more comprehensive picture of vessel anatomy on which other imaging data can be superimposed. However, image quality in the deeper region is poor because of the downgraded lateral resolution and contrast-to-noise ratio. In this study, we report on the application of an ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The hand-held UBM probe was placed on the acoustic window and scanned in a plane perpendicular to the target wires of the phantom. Under the premise of keeping the axial and lateral resolution unchanged, the phantom was used to verify the influence of the number of bits of the coded excitation on the depth of detection 33 .…”
Section: Methodsmentioning
confidence: 99%
“…The hand-held UBM probe was placed on the acoustic window and scanned in a plane perpendicular to the target wires of the phantom. Under the premise of keeping the axial and lateral resolution unchanged, the phantom was used to verify the influence of the number of bits of the coded excitation on the depth of detection 33 .…”
Section: Methodsmentioning
confidence: 99%
“…A similar problem exists when focused beams are used to synthesize emitting aperture. M. Yu et al 14 adopted virtual source SA method in a single-element IVUS system to improve image quality in depth other than the focusing depth. They overcome the limited beam width by increasing the scanning density to 1000 lines per frame.…”
Section: Eccentric Cylinder Wave Compound Imaging (Ecwc)mentioning
confidence: 99%
“…There are points that coherence-factor-based methods can improve resolution, 12,14 which should be correct for single scatterers located far from others. But for scatterers close to each other, the coherence factor (CF) gets blurred together, and scatterers could not be distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanical scanning of the transducer can provide the clinician with a high-resolution, transmural 360˚view of the tissue layers of the GI tract and is therefore of immediate interest as it can potentially provide highly detailed cross-sectional images of the GI wall. Compared with the other two solutions, mechanical rotating transducer (Figure 1c) simplifies device fabrication and electronics and is therefore particularly useful for USCE in its early development, paralleling to the development of the similar solution in intravascular ultrasound (Yu et al 2017). In a previous study, we demonstrated a mechanically scanned ultrasound capsule, shown in Figure 1c, that showed potential for clinical applications based on experimental data from ex vivo tests (Wang et al 2017b).…”
Section: Introductionmentioning
confidence: 99%